Child Friendly PAUD Classroom Design - Khoirun Nisa; Nurul Ismaiyah (Institut Agama Islam Negeri Madura, 2024)
The purpose of conducting this research is to provide information to all elements related to early childhood regarding the importance of arranging classrooms where children learn so that they are safe, comfortable and friendly. With good and appropriate planning, the objectives of the learning and stimulus will develop optimally. Please note that not everything can be used for early childhood without adult supervision. In reality, there are still many adults, especially early childhood educators, who provide room facilities without thinking about whether these facilities are safe and comfortable for children to use